2002
DOI: 10.1016/s1568-7864(02)00166-0
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumour compounds illudin S and Irofulven induce DNA lesions ignored by global repair and exclusively processed by transcription- and replication-coupled repair pathways

Abstract: Illudin S is a natural sesquiterpene drug with strong anti-tumour activity. Inside cells, unstable active metabolites of illudin cause the formation of as yet poorly characterised DNA lesions. In order to identify factors involved in their repair, we have performed a detailed genetic survey of repair-defective mutants for responses to the drug. We show that 90% of illudin's lethal effects in human fibroblasts can be prevented by an active nucleotide excision repair (NER) system. Core NER enzymes XPA, XPF, XPG,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
151
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 147 publications
(164 citation statements)
references
References 51 publications
12
151
0
1
Order By: Relevance
“…Cds1 activation triggers Rad60 phosphorylation and nuclear delocalization regulating recombination events at stalled replication forks (95). While it is yet to be determined whether CHK2 activation might also play a role in repairing irofulven-elicited DNA lesions, it has been reported that irofulven-induced DNA damage is repaired by transcription-coupled nucleotide excision repair (TC-NER) (21). Therefore, it can be speculated that the CHK2 activation by irofulven might be the result of stalled replication machinery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cds1 activation triggers Rad60 phosphorylation and nuclear delocalization regulating recombination events at stalled replication forks (95). While it is yet to be determined whether CHK2 activation might also play a role in repairing irofulven-elicited DNA lesions, it has been reported that irofulven-induced DNA damage is repaired by transcription-coupled nucleotide excision repair (TC-NER) (21). Therefore, it can be speculated that the CHK2 activation by irofulven might be the result of stalled replication machinery.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of mechanisms of irofulven action suggest that it induces DNA damage, MAP kinase activation and apoptosis (18 -20). It is also suggested that irofulven-elicited DNA lesions are mainly repaired by transcriptioncoupled nucleotide excision repair (TC-NER) (21).…”
mentioning
confidence: 99%
“…We (Koeppel et al, 2004) and others (Kelner et al, 1994;Jaspers et al, 2002) have reported that irofulven (6-hydroxymethylacylfulvene), a monofunctional covalent DNA binder (Woynarowski et al, 1997), and structurally related compounds induce DNA adducts that are exclusively recognized by TCR, but not by GGR. Here, we report that exposure of mammalian cells to irofulven is associated with potent and specific inhibition of nucleoplasmic RNA synthesis, an important decrease of Pol II mobility and a time-dependent loss of Pol II LS linked to its polyubiquitylation and proteasome-mediated degradation.…”
Section: Introductionmentioning
confidence: 89%
“…This group includes ecteinascidin-743 (ET-743, Yondelis, trabectedin), irofulven, hedamycin, and the acronycine derivative S23906. Mechanistic studies have revealed several differences in the way these compounds react with DNA-metabolizing enzymes as well as with the repair machinery (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11), which could, at least in part, explain their different activity spectra. A better understanding of the factors controlling the induction and removal of DNA damage induced by these compounds should not only facilitate their clinical application, but may also contribute to our general understanding of the structural and biological features governing adduct processing in mammalian cells.…”
mentioning
confidence: 99%